Acetylcholinesterase-inhibiting activity of salicylanilide N-alkylcarbamates and their molecular docking - Imramovsky, Ales; Stepankova, Sarka; Vanco, Jan; Pauk, Karel; Monreal-Ferriz, Juana; Vinsova, Jarmila; Jampilek, Josef (Molecules (Basel, Switzerland), 2012)
A series of twenty-five novel salicylanilide N-alkylcarbamates were investigated as potential acetylcholinesterase inhibitors. The compounds were tested for their ability to inhibit acetylcholinesterase (AChE) from electric eel (Electrophorus electricus L.). Experimental lipophilicity was determined, and the structure-activity relationships are discussed. The mode of binding in the active site of AChE was investigated by molecular docking. All the discussed compounds expressed significantly higher AChE inhibitory activity than rivastigmine and slightly lower than galanthamine. Disubstitution by chlorine in C'(₃,₄) of the aniline ring and the optimal length of hexyl-undecyl alkyl chains in the carbamate moiety provided the most active AChE inhibitors. Monochlorination in C'(₄) exhibited slightly more effective AChE inhibitors than in C'(₃). Generally it can be stated that compounds with higher lipophilicity showed higher inhibition, and the activity of the compounds is strongly dependent on the length of the N-alkyl chain.
Keywords: Cholinesterase Inhibitors; vazebná místa; salicylanilidy; Structure-Activity Relationship; Phenylcarbamates; rivastigmin; Molecular Docking Simulation; acetylcholinesterasa; Rivastigmine; molekulární modely; vztahy mezi strukturou a aktivitou; simulace molekulového dockingu; Models, Molecular; Binding Sites; Carbamates; Animals; Salicylanilides; karbamáty; Catalytic Domain; zvířata; Galantamine; galantamin; fenylkarbamáty; Electrophorus; Acetylcholinesterase; cholinesterasové inhibitory; katalytická doména